Perjalanan Digitalisasi: Membedah Sistem Penyimpanan Arsip Di Perusahaan Negara Dan Swasta Pada Masa Kini - Cindy Noviyanti; Diva Nabilah Febyona (Jurnal Manajemen Bisnis Era Digital, 2024)
This study examines the ongoing process of transitioning archive storage systems to digital formats within both governmental and private organizations, with a specific focus on assessing the benefits and drawbacks associated with digital applications. Moreover, this study also compares various aspects of archive management between state and private companies, including archive storage principles, storage systems, equipment and supplies, recording systems, lending systems, maintenance and care, and manual archive evaluation. The study utilized a descriptive approach with a qualitative method. Information was gathered through interviews pertinent to the research objectives. Findings revealed both commonalities and distinctions in the management of archives between public and private enterprises. Both types of companies use digital systems for records management, but there are differences in the applications used. Private companies use an application called Dynamics AX, which has advantages in terms of flexibility and integration with other management systems, but also has disadvantages in terms of high costs and training needs. On the other hand, state companies use the West Java Electronic Document Information System (SIDEBAR), which is more focused on administrative needs and government documentation, and has advantages in terms of accessibility and regulatory compliance, but disadvantages in terms of limited features and technical support. A further comparison shows that record-keeping systems in private companies tend to be more modern with the use of the latest technology, while state companies are more conservative with an emphasis on compliance with government regulations and standards. The equipment and supplies used by private companies are more sophisticated, while state companies prioritize simplicity and cost efficiency. In terms of loan and maintenance systems, private companies have faster and more efficient procedures, while state companies have stricter and more organized procedures. In general, this study finds that the conversion of archives into digital formats brings considerable advantages to both state-owned and private companies, though each faces unique hurdles during the process. Ongoing assessment and adjustments to systems are crucial for enhancing the effectiveness and efficiency of record management across both sectors.